Smart Piket Application to Improve Student and Teacher Discipline Productivity Based on Android - Muhammad Qadri; Muhammad Ichfan Askar; Charles S Toyani; Andryanto A (JTP - Jurnal Teknologi Pendidikan, 2025)
The problem is that the process of recording student attendance, tardiness, and violations at SMP Negeri 25 Makassar is still done manually, which has the potential to cause errors in recording, delays in conveying information, and a lack of transparency for parents. This study aims to design and develop an Android-based Smart Piket application using the Location Based Service (LBS) method as a solution to automatically record data on tardiness and violations based on time and location, which has not been implemented in the manual system. In addition, this application is equipped with a digital recap feature that can be accessed by teachers, parents, and school officials to increase transparency and speed up the flow of information on student discipline. Data collection was conducted through observation, interviews, and the distribution of questionnaires to application users. System testing was conducted using Black Box Testing and User Acceptance Test (UAT) to assess system functionality. The results of this study indicate that the Smart Piket application has functioned as expected, with a user satisfaction rate of 87.2%. It can therefore be concluded that this application is feasible and effective in improving discipline and facilitating the monitoring of student activities by schools and parents.